Sarcoidosis with Takayasu arteritis: a model of overlapping granulomatosis. A report of seven cases and literature review. (8th August 2017) - Chapelon‐Abric, Catherine; Saadoun, David; Marie, Isabelle; Comarmond, Cloé; Desbois, Anne Claire; Domont, Fanny; Savey, Léa; Cacoub, Patrice
Abstract: Objective: To describe the features of exceptional coexisting Takayasu arteritis (TA) and sarcoidosis, two conditions of unknown cause associated with a common immunologic pattern. Methods: We report seven cases of concomitant sarcoidosis‐Takayasu or Takayasu‐like vasculitis, observed in two referral centers between 1995 and 2015. Results: All patients were female. The mean age at sarcoidosis diagnosis and TA diagnosis was 36 and 37 years, respectively. Sarcoidosis occurred in 86% of cases before or together with TA. Sarcoidosis always had a classic expression except for one renal localization. Sarcoidosis was not severe and mostly non‐treated (86%). In all cases of TA, supra‐aortic arteries were involved; in only two TA cases a more diffuse inflammatory arterial involvement was noted. In one case, Takayasu arteritis occurred despite immunosuppressive therapy given for sarcoidosis. All patients received for TA a treatment with corticosteroids associated with methotrexate (four cases), infliximab (one case) or tocilizumab (one case). After a mean follow‐up of 89 months, TA always improved and no death was observed. Conclusions: TA stands as pathology associated with sarcoidosis. TA occurred in three cases among 50. When sarcoidosis preceded TA, a recovery of sarcoidosis was achieved mostly without treatment. TA is a prognostic and therapeutic factor. Immunosuppressive treatment, including steroids, led to a good prognosis for TA as well as for sarcoidosis.